SISTEM INFORMASI APLIKASI DONAT BERBASIS WEB UNTUK MENINGKATKAN DAYA SAING UMKM DI SEKTOR KULINER (Studi Kasus : Kedai Alya Donat) - Aprilia , Silva; Sujadi , Harun (Universitas Majalengka, 2025)
The development of digital technology has had a significant impact on micro, small, and medium enterprises (MSMEs), particularly in the culinary sector. This study aims to design and implement a web-based donut sales application information system as a solution to increase the competitiveness of Kedai Alya Donuts. The system development method used is the Waterfall method, starting with needs analysis, system design using UML, implementation using PHP, CSS, and JavaScript programming languages, and system testing using the Black Box method. The developed system allows administrators to manage product data and receive orders in an integrated manner via WhatsApp, while customers can easily access product information and place orders. The implementation results indicate that this system can expand market reach and improve sales process efficiency, thus potentially strengthening Kedai Alya Donuts' competitiveness in the digital era.